Public Information and Education in the Promotion of Highway Safety - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2007)
TRB's National Cooperative Highway Research Program (NCHRP) Research Results Digest 322: Public Information and Education in the Promotion of Highway Safety assesses the role of public information and education programs in contributing to behavior change in the highway safety area.
Keywords: Transportation and Infrastructure

Plans and Practices for Groundwater Protection at the Los Alamos National Laboratory: Final Report - National Research Council (The National Academies Press, 2007)
The world's first nuclear bomb was a developed in 1954 at a site near the town of Los Alamos, New Mexico. Designated as the Los Alamos National Laboratory (LANL) in 1981, the 40-square-mile site is today operated by Log Alamos National Security LLC under contract to the National Nuclear Security Administration (NNSA) of the U.S. Department of Energy (DOE). Like other sites in the nation's nuclear weapons complex, the LANL site harbors a legacy of radioactive waste and environmental contamination. Radioactive materials and chemical contaminants have been detected in some portions of the groundwater beneath the site. Under authority of the U.S. Environmental Protection Agency, the State of New Mexico regulates protection of its water resources through the New Mexico Environment Department (NMED). In 1995 NMED found LANL's groundwater monitoring program to be inadequate. Consequently LANL conducted a detailed workplan to characterize the site's hydrogeology in order to develop an effective monitoring program. The study described in Plans and Practices for Groundwater Protection at the Los Alamos National Laboratory: Final Report was initially requested by NNSA, which turned to the National Academies for technical advice and recommendations regarding several aspects of LANL's groundwater protection program. The DOE Office of Environmental Management funded the study. The study came approximately at the juncture between completion of LANL's hydrogeologic workplan and initial development of a sitewide monitoring plan.
Keywords: Environment and Environmental Studies

Review of the Space Communications Program of NASA's Space Operations Mission Directorate - National Research Council (The National Academies Press, 2007)
The Space Communications Office (SCO) at NASA has two primary roles. The first is to manage two of the communications networks that enable spaceflight operations and research, and the second is to integrate agency-wide telecommunications issues. In 2005, NASA asked the NRC to review the effectiveness of the SCO in carrying out its responsibilities by assessing the overall quality of the space communications program. This report presents a review of each of the program elements within the SCO—the space network, NASA’s integrated space network (NISN), spectrum management, standards management, search and rescue, communications and navigation architecture, technology, and operations integration. The review focuses on formulation of plans for each element, plan development methodology, connections with the broader community, and overall capabilities. Recommendations for improving SCO operations and organization are provided.
Keywords: Space and Aeronautics

Ethical and Legal Considerations in Mitigating Pandemic Disease: Workshop Summary - Institute of Medicine (The National Academies Press, 2007)
In recent public workshops and working group meetings, the Forum on Microbial Threats of the Institute of Medicine (IOM) has examined a variety of infectious disease outbreaks with pandemic potential, including those caused by influenza (IOM, 2005) and severe acute respiratory syndrome (SARS) (IOM, 2004). Particular attention has been paid to the potential pandemic threat posed by the H5N1 strain of avian influenza, which is now endemic in many Southeast Asian bird populations. Since 2003, the H5N1 subtype of avian influenza has caused 185 confirmed human deaths in 11 countries, including some cases of viral transmission from human to human (WHO, 2007). But as worrisome as these developments are, at least they are caused by known pathogens. The next pandemic could well be caused by the emergence of a microbe that is still unknown, much as happened in the 1980s with the emergence of the human immunodeficiency virus (HIV) and in 2003 with the appearance of the SARS coronavirus. Previous Forum meetings on pandemic disease have discussed the scientific and logistical challenges associated with pandemic disease recognition, identification, and response. Participants in these earlier meetings also recognized the difficulty of implementing disease control strategies effectively. Ethical and Legal Considerations in Mitigating Pandemic Disease: Workshop Summary as a factual summary of what occurred at the workshop.
Keywords: Health and Medicine